2018
DOI: 10.3390/risks6040143
|View full text |Cite
|
Sign up to set email alerts
|

Firm’s Risk-Return Association Facets and Prospect Theory Findings—An Emerging versus Developed Country Context

Abstract: A risk-return association under normal market conditions can be conventional positive (risk-averse) or "paradoxical" negative (risk seeking). This study has the objective to investigate whether such an association is stable across market trends (i.e., bull and bear) and for overall, industry-classified and partitions sub-samples after controlling for a firm's age, size, leverage and liquidity using operating performance risk-return measures. In total, this study analyses 2666 firms (1199 firms from 15 develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 73 publications
2
25
0
Order By: Relevance
“…To establish the convergent validity of our tests, we employed two most commonly used two proxies, i.e. return on assets (ROA) and return on equity (ROE) (Andersen, 2008; Gupta and Pathak, 2018; Holder et al. , 2016; Jegers, 1991).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish the convergent validity of our tests, we employed two most commonly used two proxies, i.e. return on assets (ROA) and return on equity (ROE) (Andersen, 2008; Gupta and Pathak, 2018; Holder et al. , 2016; Jegers, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Among this, firm size and financial leverage are the most significant factors that affect businesses across various countries (Arrfelt et al. , 2018; Gupta and Pathak, 2018). For firm size (FSize), we use the natural logarithm of firm sales (Aldrich, 1999; Brick et al.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this, we divide the entire study period in crisis and non-crisis subperiods based on existing literature in finance (DasGupta, 2017a, b;Ranajee et al, 2018;Gupta and Pathak, 2018). We do such bifurcation of the study period in order to assess the impact of worldwide economic turbulence on cross-country dividend payouts levels and further to assess the predictive consistency of determinants though periods of stability and turbulence.…”
Section: Methodsmentioning
confidence: 99%
“…By using the local linear estimator, the study demonstrated that lower market values are related to higher operational inefficiencies, whereas higher market values are associated with higher operating efficiencies. Gupta and Pathak (2018) stated that under normal market conditions, a risk-return relationship might be conventionally positive (risk-averse) or "paradoxically" negative (risk seeking). Xing and Yu (2018) argued that financial crises during the previous few decades have revealed the enormous impact of market structural breaks on firms' lending behavior.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%